Prevalence and Patterns of Upper and Lower Third Molar Impaction: A Radiographic Retrospective Study based on a population in Erbil, Iraq. - Layla Muhammad Fatah; Ali F. Alzubadee; Ribwar F. Khalid; Abduljaleel Samad; Reiad Al-Kamali (Erbil Dental Journal)
Background and objective: The most impacted teeth in the human oral cavity are the lower third molars. Although they may cause pathology, the unerupted teeth are not pathogenic lesions by themselves. Impaction can manifest at various degrees and in various patterns.